The Game Changer :How Every Leader can Drie every day Innovation. - A G Lafley (Penguin Books, 2008)
It is by making innovation an intimate, intentional part of the business that A. G. Lafley - the Jack Welch of the 21st century - has recently transformed Procter & Gamble from a $39 into a $76 billion dollar company that touches more than 3 billion people around the world. On the brink of collapse when he joined in 2000, it became a model for growth and innovation. In this inspiring and practical book Lafley explains how making innovation more than just a stand-alone activity enabled him to turn around growth, productivity and the bottom line. As this book shows, innovation can become a reliable and repeatable game-changer for any business in all areas of the organisation, from the CEO's desk to the everyday activities of each employee. By using new insights and easy-to-relate-to stories from P&G and other companies - describing, for example, the best way to brainstorm, and the "innovation portfolio" - this book is destined to become as influential as Good to Great and as Charan's own bestseller, Execution.